Delusion or Faith? Exploring Religious Delusions in Individuals with Schizophrenia within the Banjar Culture - Mustafa, Nabila Regita Putri; Maisyarah, Nur’Aulia; Maulidina, Aulia; Aditya, Muhammad Reza; Shadiqi, Muhammad Abdan (UI Scholars Hub, 2025)
Schizophrenia is often characterized by delusions and hallucinations, which often appear as manifestations of religious delusions in the Banjar cultural context. This phenomenon can be understood through the hyper-religiosity theory, which explains excessive religious behavior in individuals with schizophrenia. This qualitative case study aims to identify the forms of religious delusion in individuals with hyper-religiosity and the underlying causal factors. Data were collected through in-depth interviews and observations with 10 informants, comprising four individuals with religious delusions selected using purposive sampling based on their experience of studying Tasawwuf and experiencing religious delusions and six significant others. The findings show that delusions appear in the form of recognition as God or Prophet, receiving divine knowledge, and hyper-religiosity behavior seen in excessive worship practices, intolerance of different beliefs, and fanaticism toward religious symbols. Contributing factors include genetic predisposition, medication non-adherence, and traumatic experiences, which intensify psychological symptoms and demonstrate the complex interactions among cultural, psychological, and biological factors. These findings underscore the importance of clinical approaches that are sensitive to the cultural and religious contexts of patients and the need for further research to develop more effective intervention strategies to address religious delusions in individuals with schizophrenia in religious communities.